PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KPUASAN KONSUMEN DODOL BUAH UD PUTRA MANDIRI DI KABUPATEN SIAK (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study was to determine how much influence price and quality had on consumer satisfaction of dodol buah at UD Putra Mandiri in Siak Regency. The data collected in this study is primary data using a questionnaire or questionnaire. The research sample is consumers (people who buy) fruit lunkhead UD Putra Mandiri as many as 72 consumers. The data analysis technique uses quantitative descriptive analysis, hypothesis testing consisting of multiple linear regression analysis, partial test (t test), simultaneous test (f test) and the coefficient of determination. The results of the study found that price and product quality had a positive and significant effect on consumer satisfaction. The R square value of 0.780 or 78.0 means that this shows that the price and product quality variables together contribute to consumer satisfaction of 78, 0%, while the remaining 22.0% is influenced by other factors not included in the study.Key Words: Price, Product Quality, Consumer Satisfaction